Institutionalization of E-commerce in Women-led SMEs - A Least-developed Country Context - Matsinhe, Fernanda Ernestina (Department of Information Systems, 2019)
This dissertation reported an investigation of e-commerce institutionalization process in women-led SMEs in Mozambique. The goal was to understand how e-commerce is conceptualized by these SMEs while exploring the contextual factors that contribute or inhibit the process of institutionalization from the unique perspective of a least developed country (LDC) such as Mozambique. The study combined the perspectives offered by the contextualist theory (Pettigrew, 1985) and the Perceived E-readiness Model (PERM) (Molla & Licker, 2005a) to employ an integrated framework for investigating the process of e-commerce institutionalization. An interpretative and qualitative multiple case study approach was employed as a methodological basis, using six SMEs which have been able to institutionalize e-commerce. The data collection was conducted through multiple data sources including semi-structured interviews, analysis of company website, and social media platforms. Data were analysed using a thematic analysis approach across the cases. The findings indicate that there are different patterns of e-commerce institutionalization. SMEs do not always follow the traditional steady stages of e-commerce growth described in the literature. Furthermore, the results showed a socially constructed feature of e-commerce characterized by the extensive use of social media networks. A great levels of institutionalization and satisfaction was attained when enabling factors within and outside the organization interacted positively. Within the internal context of the organizations, the SMEs manager’s capability to use social media networks, e-mail and mobile phones to build innovative business models, create direct relationships with customers, and marketing direct to their niche markets. Factors from the external context emerged as the main challengers to the process of institutionalization, specifically the challenges faced by the government, market forces, supporting industries, and those of sociocultural nature. A number of important recommendations were made, for example, the government should not only provide the regulatory framework but also work actively in its promotion and implementation. This should encompass the establishment of networks and training opportunities to improve SMEs knowledge regarding e-commerce, and continuous partnership between the various stakeholders involved in the e-commerce ecosystem in addressing the various environmental challenges. By conducting an investigation on the selected women-led SMEs in Mozambique, this study has extended knowledge of e-commerce research in the country. Additionally, it is an important contribution for the debate about e-commerce in developing countries, specifically a better understanding of SMEs that go beyond the initial adoption phase.